A ética na formação de professores da educação básica - Ceretta, Patrício (2018)
The dissertation “Ethics in the Formation of Teachers of Basic Education”, presented to the Masters Course of the Post-Graduation Program in Education, in the line of research: Formation, Knowledge and Professional Development, reflects upon the importance of Ethics in the formation of teachers, with a special attention to: identifying the spaces and times dedicated to the study of Ethics during the teacher formation of pedagogy courses and others of faculty formation; stemming from a comprehension of Ethics, arguing about the importance of the academic study of it, both in it’s systematical aspects, as well as in the knowledge of the philosophical theories about moral, to show that both provide fundamental elements to the comprehension of the practice of teachers; contributing to the formation of educational professionals who are autonomous and thoughtful in relation to their praxis and the social and political repercussion of it. The research question asks why Ethics, as an academic discipline, is fundamental in the formation process of the Teacher Formation Courses to the basic education, in general and specifically in the Pedagogy Courses. The Philosophical Hermeneutics, of Hans-Georg Gadamer, serves as a theoretical and methodological reference in the attempt to answer said question and pursue the before mentioned objectives. It is a bibliographic and interpretative research, in conversation with authors such as Adolfo Sanchez Vazquez, Adela Cortina, Edgar Morin, Enrique Dussel, Boaventura de Souza Santos and Leonardo Boff. In the final part of this work, it is raised the suspicions that the lack of this thematic in the formation may result in the dehumanisation of the relationships, that leads to the banalization, aggressiveness and violence in the pedagogical relationships and show that an Ethics of Alterity would help in recovering the solidarity and care commitment towards others and the world. This research is expected to challenge educators to pay more attention to the ethical and political implications of their praxis and to contribute to a more thoughtful reflection about behavior itself, through the access to thematizations about it, others and the world.